Research on K-means Clustering Algorithm Based on MapReduce Distributed Programming Framework - Zhang, Ling (Procedia computer science, 2023)
As a classical clustering algorithm, K-means algorithm has a profound research background. In the of big data era, K-means algorithms will play a greater advantage, being able to quickly divide similar data into the same cluster. Combining K-means algorithm with MapReduce distributed computing framework and running on Hadoop big data platform can significantly improve the clustering effect. Based on MapReduce framework structure, this paper studies K-means model, including K-means principle, distance calculation, content validity index and external validity index. On this basis, the K-means clustering flow based on MapReduce big data programming framework is proposed, and the execution process of the algorithm flow is described in detail, which provides a guide for the algorithm implementation.